Planktonic foraminifera and calcareous nannofossils at the Cretaceous-Tertiary contact in Zululand - Stapleton, R P (Bernard Price Institute for Palaeontological Research, 1975)
Assemblages of planktonic foraminifera and calcareous nannofossils for the Maestrichtian and Danian of Zululand are listed and illustrated. The Globotruncana gansseri and G. mayorensis foraminiferal zones are present in the Maestrichtian. The Globigerina triloculinoides and Globorotalia compressa foraminiferal subzones are present in the Danian. The Maestrichtian in this area cannot be subdivided on the basis of calcareous nannofossils. Danian nannofossil zones present are those of Cruciplacolithus tenuis and Chiasmolithus danicus . The Cretaceous-Tertiary faunal extinctions are briefly discussed and it is concluded that lowered temperatures were a factor in this extinction.
Keywords: K/T boundary; climate change; Marine fossils